2014
DOI: 10.1080/07391102.2014.893203
|View full text |Cite
|
Sign up to set email alerts
|

A new insight into mushroom tyrosinase inhibitors: docking, pharmacophore-based virtual screening, and molecular modeling studies

Abstract: Tyrosinase, a widely spread enzyme in micro-organisms, animals, and plants, participates in two rate-limiting steps in melanin formation pathway which is responsible for skin protection against UV lights' harm whose functional deficiency result in serious dermatological diseases. This enzyme seems to be responsible for neuromelanin formation in human brain as well. In plants, the enzyme leads the browning pathway which is commonly observed in injured tissues that is economically very unfavorable. Among differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…Tyrosinase plays a crucial role in melanin biosynthesis pathway that is responsible for melanogenesis of animals [3]. And it actually catalyzes the hydroxylation of tyrosine to L-DOPA (L-3, 4-dihydroxyphenylalanine) and the subsequent oxidation of L-DOPA to DOPA quinone [4,5] which transforms into melanin and other polyphenolic compounds after a series of spontaneous chemical reactions [6].…”
Section: Introductionmentioning
confidence: 99%
“…Tyrosinase plays a crucial role in melanin biosynthesis pathway that is responsible for melanogenesis of animals [3]. And it actually catalyzes the hydroxylation of tyrosine to L-DOPA (L-3, 4-dihydroxyphenylalanine) and the subsequent oxidation of L-DOPA to DOPA quinone [4,5] which transforms into melanin and other polyphenolic compounds after a series of spontaneous chemical reactions [6].…”
Section: Introductionmentioning
confidence: 99%
“…The pK a was calculated by the PROPKA 3.1 web server to determine which residue was more likely to adopt non-standard ionization states [27]. The main structural water molecules in the active site were kept [28]. Protein topology parameters were obtained by the GROMOS96 53a6 force field as well as the simple point charges (SPC) water model.…”
Section: Molecular Dynamic Simulationmentioning
confidence: 99%
“…Although the double reciprocal analysis of the kinetic data produced convex graphs with negative curvature, indicating the dominancy of negative cooperativity, Hill analysis of the data suggested that negative cooperativity was dominant at low Although the assumption of mixed-type cooperativity shed light on the complex kinetics of MT activities, changes in the mode of inhibition and the advent of non-competitive and mixed-type modes of inhibition in various studies have led scientists to assume the existence of a regulatory site on MT [9,10,[24][25][26]. However, a literature review reveals that, despite the reports of MT crystal structures (with and without an inhibitor) [27] and some valuable molecular docking and simulation studies [28], no allosteric/regulatory site for MT has been reported. To explain non-competitive and mixed-type modes of inhibition in MT kinetics studies, it is necessary to explain how the ternary complex of substrate/MT/effector is formed during the enzymatic reactions.…”
Section: Introductionmentioning
confidence: 96%